Microcells for metastructures: an application of microSystem technology to distributed space structures - Lecuyot, Arnaud (Cranfield University, 2004)
In this thesis, a new concept of space systems called metastructures is studied. Applications are in very large space structures (1 km) that can take many shapes and be reconfigured during operations. This concept is explored by defining it from a systems engineering perspective, characterising the system dynamics and technical baseline, and assessing its interest with respect to proposed missions and to alternatives. Metastructures are defined as assemblies of microcells linked rigidly. Microcells are themselves defined as Nanosatellites with reduced functionalities, and are referenced locally or globally for active position control within the metastructure. Two reference missions are considered, a centimetric interferometer and a Solar concentrator as part of Solar Power systems. The methods used to analyse these missions and achieve the research objectives are based on strategy analysis, standard practices in mission and system design, and a simplified system dynamics simulation implemented in a custom simulator. The analysis of dynamics demonstrates the controllability of such structures, and their ability to maintain and keep shape in most orbits to good accuracy. It also shows that the design of the distributed controller is important. From this, subsystem requirements are derived for the microcells which are studied as highly integrated microsystems. Mass of the microcells is around 500 g, much of which is propellant. The baseline system configuration for reference missions is derived, including costing. For these missions masses are less than a ton, with costs less that 500 Million Euros. Metastructures do not perform well in terms of lifetime given the simplistic controller used. Appropriate research of decentralised controllers may remedy to this, but a weak point of the concept is that of stowing and launching. Finally, a preliminary analysis of the concept with respect to its alternatives tends to show that it is worthy of further investigation.